2018
DOI: 10.1029/2018gl078386
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Level and Surface Circulation Response to the Arctic Oscillation

Abstract: The Arctic Oscillation (AO) is the leading mode of extratropical northern hemisphere atmospheric variability, affecting surface pressure, winds, temperature, and precipitation. Here we use an altimeter sea level record spanning 2003–2014, covering the ice‐covered and ice‐free ocean, to examine the influence of the AO on Arctic sea level and surface geostrophic circulation. AO‐driven alongshore wind anomalies drive cross‐shelf Ekman transport and opposing barotropic sea level anomalies between the shelf seas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
5
40
1
Order By: Relevance
“…Alkire et al () point out the large interannual variability in surface salinity in the central Arctic, partly attributed to shifts in the alignment of the TPD. Several studies document the contribution of the Arctic Oscillation index in the shifts of the TPD and Arctic general surface circulation (Alkire et al, ; Armitage et al, ; Morison et al, ). However, the relationship between Arctic Oscillation and river runoff pathways in the present data set remains unclear.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Alkire et al () point out the large interannual variability in surface salinity in the central Arctic, partly attributed to shifts in the alignment of the TPD. Several studies document the contribution of the Arctic Oscillation index in the shifts of the TPD and Arctic general surface circulation (Alkire et al, ; Armitage et al, ; Morison et al, ). However, the relationship between Arctic Oscillation and river runoff pathways in the present data set remains unclear.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The current work focuses on only the contributions of SSTAs in the tropical Pacific and NA oceans, which can explain only part of the SPC variance. Other factors, such as the SSTAs in the Indian Ocean, snow cover over the Eurasian continent, sea ice over the polar region, anomalous Tibetan Plateau heating, and greenhouse gases, may also contribute to the interdecadal change in the SPC variation (e.g., Armitage et al, ; Dunstone et al, ; Jia et al, ; Li et al, ; Menon et al, ; Xing & Huang, ). For example, some recent studies (Armitage et al, ; Dunstone et al, ; Xing & Huang, ) have revealed that the sea ice concentration in the Arctic during the preceding autumn might signify anomalous NAO and SST conditions in the NA, which can persist until early summer and affect EA precipitation in May–June.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…HE Cryosat-2 Synthetic Aperture Interferometric Radar Altimeter (SIRAL) has proven an immensely successful tool for monitoring global ice and ocean properties. It has allowed us to estimate interannual ice sheet mass balance [1], the global marine gravity field [2] circulation [3,4], and sea ice thickness [5,6], with unprecedented spatial coverage, frequency and accuracy. Recent work has demonstrated that sea ice extent is closely tied to the inter-seasonal 'memory' of ice thickness [7], which means that sea ice models initialized with thickness observations can substantially improve the skill of ice extent forecasts [8,9,10].…”
Section: Introductionmentioning
confidence: 99%